Overexpression and Biochemical Properties of a GH46 Chitosanase From Marine Streptomyces hygroscopicus R1 Suitable for Chitosan Oligosaccharides Preparation - Wang, Jianrong; Wang, Ping; Zhu, Mujin; Chen, Wei; Yu, Si; Zhong, Bin (Frontiers in Microbiology, 2022)
Due to the various biological activities of chitosan oligosaccharides (COSs), they have great potential value for use in many areas. Chitosanase plays an important role in enzymatic preparation of COSs. Herein, a gene encoding a chitosanase (ShCsn46) from marine Streptomyces hygroscopicus R1 was cloned and the sequences encoding ShCsn46 without signal peptide were optimized based on the codon usage of Pichia pastoris (P. pastoris). In addition, the optimized gene was ligated to pPICZαA and transformed to P. pastoris X33. After screening, a recombinant strain named X33-Sh33 with the highest activity was isolated from 96 recombinant colonies. The maximum activity and total protein concentration of the recombinant strain ShCsn46 were 2250 U/ml and 3.98 g/l, respectively. The optimal pH and temperature of purified ShCsn46 were 5.5 and 55°C, respectively. Meanwhile, ShCsn46 was stable from pH 5.0 to 10.0 and 40 to 55°C, respectively. The purified ShCsn46 was activated by Mn2+ and inhibited by Cu2+, Fe2+, and Al3+. In addition, substrate specificity of the purified ShCsn46 showed highest activity toward colloidal chitosan with 95% degree of deacetylation. Furthermore, the purified ShCsn46 exhibited high efficiency to hydrolyze 4% colloidal chitosan to prepare COSs. COSs with degree of polymerization of 2–6, 2–5, and 2–4 were controllably produced by adjusting the reaction time. This study provides an excellent chitosanase for the controllable preparation of COSs with a desirable degree of polymerization.